the OBSTETRIC CARE MANAGEMENT OF NEWBORNS WITH HYPOGLYCEMIA IN THE PICU NICU - Nasution, Malinda Natasya; Sri Juwita Stefany Pardosi; Marlina Tafonao; Polmaria Metawati Panjaitan; Siti Alza (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Hypoglycemia in newborns is a metabolic emergency characterized by low blood glucose levels due to an imbalance between glucose production and utilization. This condition often occurs in neonates with risk factors such as babies born to mothers with diabetes mellitus, high birth weight, prematurity, or impaired metabolic adaptation after birth. Objectives: This study aims to provide an overview of the implementation of midwifery care for a 4-day-old infant with hypoglycemia in the PICU of Haji General Hospital, Medan, in 2025. Methods: The study used a case study with a midwifery care management approach based on Varney’s 7 steps, which include data collection, problem identification, planning, implementation, and evaluation. Data were obtained through observation, physical examination, and measurement of the infant’s blood glucose level. Results: The study showed that the infant experienced hypoglycemia with an initial glucose level of 33 mg/dL, accompanied by symptoms of weakness and a decreased sucking reflex. Management included administering a 10% glucose bolus, D10W infusion, keeping the infant warm, and gradually introducing breast milk. After intervention, the baby’s condition improved, with glucose levels returning to normal (82 mg/dL), increased activity, and a good sucking reflex. Conclusions: This case demonstrates that prompt, appropriate, and continuous management of neonatal hypoglycemia can improve the baby’s condition and prevent further complications. The role of healthcare workers, particularly midwives, is crucial in early detection and close monitoring of neonates at risk of hypoglycemia.